Optimalisasi Motorik dan Pemahaman IPAS Siswa melalui Permainan Hula Hoop Inovatif dalam Kegiatan Pramuka Siaga di MIS Dadirejo - Atiyah Atiyah (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
This study aims to integrate the learning of Natural and Social Sciences (IPAS) with the traditional hula hoop game in Pramuka Siaga extracurricular activities at MIS Dadirejo. The research employs a qualitative approach with a descriptive design. The subjects of the study include fourth and fifth-grade students actively participating in Pramuka activities. Data collection techniques involve observation, interviews, and documentation. The findings reveal that the innovative use of hula hoop games can enhance students' motor skills, such as body coordination and balance, as well as their understanding of concepts like force, energy, and gravity taught in IPAS subjects. The implications of this study emphasize the importance of integrating traditional games into active learning to simultaneously improve students' physical and academic skills.